Our experience of interdisciplinary work in domestic violence and child abuse in the province of Espinar (Cusco) - Sánchez, Carolina Inés (2003)
The problem is in us. Violence and abuse in the family is not an isolated phenomenon, as we have insisted on believing for so long, since the index and the statistics defy our incredulity. If we delve into reality, we will find a complex, multifaceted and widespread phenomenon: marital violence, child abuse, domestic sexual abuse, abuse of the elderly and the disabled... these are some of its most frequent manifestations. We find it in all social classes and at all socio-educational levels. It takes many forms: physical abuse, psychological abuse, sexual abuse, abandonment and neglect.